Biomedical investigation and informed consent in vulnerable populations and individuals - la Rocca, Susana; Martínez, Gladys; Rascio, Alejandra; Bajardi, Mirta (Acta Bioethica, 2005)
The economical and political transnationality context inside which today’s biomedical investigations take place favours the phenomenon known as life’s medicalization and raises both countries’ and individuals’ vulnerability. If we assume that the need to protect the subjects of investigation is bioethics’ accepted responsibility, and, first of all, of the most vulnerable ones, these aspects should be taken into special consideration and evaluation in order to correct them, if needed.